Strategi Kolaboratif Pengembangan Ekowisata Puncak Marindal di Kampung Wawiyai Kabupaten Raja Ampat - Mei Merlince Gimlah; Sattu Sattu; Wahyudin Halik; Fauziah Saragih (LRI Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze the Marindal Peak Ecotourism Development Strategy in Wawiyai Village, Raja Ampat Regency. Ecotourism is a form of sustainable tourism development that emphasizes the preservation of the natural and cultural environment through collaboration between the government, community, managers and other stakeholders, as well as providing economic benefits to the local community. The qualitative research method with a descriptive type and data collection techniques through observation, interviews, literature reviews and documentation. The results of the study indicate that a collaborative strategy with the formation of an organizational structure implemented between the government community and managers by conducting coordination and participation. While the program strategy focuses on implementation in decision making, natural resource management and infrastructure development, training and socialization. Some of the main factors or obstacles, namely the low participation of the community and village government, the lack of supporting facilities such as restaurants, lodging, internet networks, and sea transportation, and the lack of community understanding of ecotourism potential. However, there are supporting factors in the form of attractive natural potential, visitors can enjoy the beautiful sunset in the afternoon. The development strategy with the implementation of this collaborative strategy, the development of Marindal Peak ecotourism is expected to run effectively and sustainably so as to provide economic benefits and improve the welfare of the local community.